2006
DOI: 10.1055/s-0038-1634112
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Number of Cancer Patients Hospitalized in a Geographic Area Using Claims Data without a Unique Personal Identifier

Abstract: We provide a good estimate of the morbidity in acute care hospitals using claims data that is not linked to individual patients. This estimate reflects the medical activity and can be used to anticipate acute care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Among the claims-only studies, there was very little reported use of either a previously published algorithm (n ¼ 8, 12.9%) [20,27,37,48,49,58,60,61] or a validated algorithm (n ¼ 4, 6.5%) [48,58,60,61]. Almost half (n ¼ 31, 48.4%) of claims-only studies relied solely on diagnosis codes to select their study sample [7,9,[12][13][14][15]19,20,25,[27][28][29]31,32,34,47,49,50,56,59,60,63,69,70], with 35.5% (n ¼ 11) of these studies using a single claim with a cancer diagnosis as a prerequisite for study entry [15,29,32,34,36,37,46,50,63,69,70]. Only 4.8% of the articles discussed the implications of their selection criteria on the study findings…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…Among the claims-only studies, there was very little reported use of either a previously published algorithm (n ¼ 8, 12.9%) [20,27,37,48,49,58,60,61] or a validated algorithm (n ¼ 4, 6.5%) [48,58,60,61]. Almost half (n ¼ 31, 48.4%) of claims-only studies relied solely on diagnosis codes to select their study sample [7,9,[12][13][14][15]19,20,25,[27][28][29]31,32,34,47,49,50,56,59,60,63,69,70], with 35.5% (n ¼ 11) of these studies using a single claim with a cancer diagnosis as a prerequisite for study entry [15,29,32,34,36,37,46,50,63,69,70]. Only 4.8% of the articles discussed the implications of their selection criteria on the study findings…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…Examplesofresearch on thistopic by the authors areg iven in [25][26][27]a nd,i na somewhat broaderrange,but still closeand related, in [33][34][35][36][37][38][39][40][41]. Other examples of relatedr esearch,p resented in recentp ublicationsinthis journal, arein [42,43] discussing medical data management andelectronic patient records relatedtopatient data presentation,in [44][45][46], to health information systems, in [47] and [ 48] to patientgroup analysis, in [49] to coding, in [50][51][52] to ICT tools, in [53][54][55]tocooperative care andt ransinstitutionalh ealth information systems, in [56] and [ 57] to knowledgebased decision support, in [58] to software engineering, in [59] to user interfacing, in [60] to newdatatypes, in [61] to authentification as well as in [62] and [63] to newinformation andc ommunication technologies. Then ecessity of futurer esearch on the electronic patientrecord with its various sidesismentioned in [64].…”
Section: How To Lecture Medical Datamanagement?mentioning
confidence: 99%
“…In recent years, the number of compensation claims for medical injuries have increased due to the greater expectation and awareness of patients. The analysis of medical injuries compensation claims is a very helpful way to estimate risk [10], because these data contain information about the department/ unit where the injury happened, the estimated costs of the injury as well as the occurrence of the claims over the years [11][12][13]. Furthermore, compensation claims are readily available data, unlike data strictly related to clinical errors, which are hardly collected.…”
Section: Introductionmentioning
confidence: 99%